PHYSICO - MICROBIOLOGICAL EXAMINATIONS OF DOMESTIC WATER USED BY THE COMMUNITY OF COLLEGE OF AGRICULTURE AND ITS ENVIRONS, MAIDUGURI, NORTH – EASTERN NIGERIA - Abubakar Biu, Abdullahi; Mohammed, Gwana Adamu; Kofar Na’isa, Mu’azu Abdullahi; Musa, Abubakar; Aliyu, Abubakar; Marte, Mohammed Lawan (International Journal of Research -GRANTHAALAYAH, 2020)
This research study focuses on the importance to evaluate the types and their quality, beneficial uses of waters in order to ascertain its assess, contaminations and the impacts of pollution. Study was conducted on Physico - microbiological examinations of domestic water used by the Community of College of Agriculture and its environs, Maiduguri. Methods used were that described by Cheesbrough [1], Gwana et al., [2], and AOAC [3]. 200 mls of water sample from 8 water stations (A to H) were each sampled. Results obtained revealed the colour, odour and taste of the water sampled were normal, except station E, which was brownish in colour and perceived fishy smelt and tasted salty, mean pH values ranged from of 6.6 to 8.2, mean temperature (OC) from ranged from 22.1 to 32.1 OC, mean turbidity (TU) from ranged from 1 to 4 TU. Microscopical examination of the water sampled in each of the stations using parasitological techniques; there was no protozoan cysts, protozoan trophozoites, helminths ovae (eggs) and helminths adult parasites found, except in water station E where larva of Schistosoma species (Bifurcated Cercaria) was seen. For the bacteriological examination, the indicators used were Coliform, Escherichia coli, and Aerobic mesophilic bacteria, values were given in mean coliform unit per mills (CFU / mls) of the water sampled. Stations; A and B, had yielded growth of coliform each with 0, C, F, G and H each had 1, D (5), and E (94). Escherichia coli; station A had 1, and B, C, F, and G had 0 each, 22, 56, and 18 for D, E, and H. Aerobic mesophilic bacteria; station A had 283, B (23), C (103), D (261), E (313), F (51), G (11) and H had 286 CFU / mls. The water stations were found free from health hazards, therefore, fit for consumption and domestic activities, except water from station E. There is a needs to be enlightened the community on safe - drinking water measures in the study area.